When less is heard than meets the ear: Change deafness in a telephone conversation - Fenn, Kimberly M.; Shintel, Hadas; Atkins, Alexandra S.; Skipper, Jeremy I.; Bond, Veronica C.; Nusbaum, Howard C. (Quarterly journal of experimental psychology (2006), 2011)
During a conversation, we hear the sound of the talker as well as the intended message. Traditional models of speech perception posit that acoustic details of a talker's voice are not encoded with the message whereas more recent models propose that talker identity is automatically encoded. When shadowing speech, listeners often fail to detect a change in talker identity. The present study was designed to investigate whether talker changes would be detected when listeners are actively engaged in a normal conversation, and visual information about the speaker is absent. Participants were called on the phone, and during the conversation the experimenter was surreptitiously replaced by another talker. Participants rarely noticed the change. However, when explicitly monitoring for a change, detection increased. Voice memory tests suggested that participants remembered only coarse information about both voices, rather than fine details. This suggests that although listeners are capable of change detection, voice information is not continuously monitored at a fine-grain level of acoustic representation during natural conversation and is not automatically encoded. Conversational expectations may shape the way we direct attention to voice characteristics and perceive differences in voice.